Heavy metal pollution and health risk assessment in upland and riparian soils of the Ganga River basin - Sanchit Kumar; Anshumali (Discover Soil)
Abstract Riparian zones act as crucial sinks for heavy metals (HM), with spatial distribution influenced by landscape positioning and land-use practices. This study investigated the mineralogical composition, HM contamination, and associated risks in the upland and riparian soils of the Ganga River basin. A total of 56 composite soil samples (0–20 cm depth) were collected from five land-use types: uplands (undisturbed forest: CALref; conventional agriculture: CAL) and riparian zones (reservoir: RSRZ; river: RRZ; uncultivated: RZref). Statistical analysis revealed significantly (P < 0.05) higher concentrations of HM in cultivated soils (CAL, RSRZ, RRZ) compared to reference soils (CALref, RZref). Pollution indices (I geo , EF, and CF) revealed high soil contamination by Cd > As > Ga, particularly in riparian soils. Ecological risk assessment identified high potential risks (PERI > 600) in the cultivated riparian soils (RSRZ: 766, RRZ: 620) than in other soils, primarily contributed by Cd (> 85%). Health risk assessment revealed that cultivated riparian soils pose significant non-carcinogenic (THI: 1.55–1.73) and carcinogenic risks (TCR: 1.06 × 10–4–1.13 × 10–4) for children, primarily due to Cr and As exposure. The dominant exposure pathway of the HM was ingestion (> 88%), which was higher for children than adults. Source apportionment analysis identified mixed anthropogenic sources (36.2%), geogenic origins (26.5%), and specific agricultural inputs (9.8%) as primary factors controlling the HM distribution. The study emphasizes the impact of agricultural-induced land use changes on HM contamination in riparian soils, increasing the risk of exposure and toxicity to local communities dependent on riparian resources.